Enhanced binding capability of nuclear factor-κB with demethylated P2X3 receptor gene contributes to cancer pain in rats. Issue 10 (October 2015) - Zhou, You-Lang; Jiang, Guo-Qin; Wei, Jinrong; Zhang, Hong-Hong; Chen, Wei; Zhu, Hongyan; Hu, Shufen; Jiang, Xinghong; Xu, Guang-Yin
Abstract : Abstract: Nuclear factor-kappa B (NF-κB) signaling is implicated in both cancer development and inflammation processes. However, the roles and mechanisms of NF-κB signaling in the development of cancer-induced pain (CIP) remain unknown. This study was designed to investigate the roles of the p65 subunit of NF-κB in regulation of the purinergic receptor (P2X3R) plasticity in dorsal root ganglion (DRG) of CIP rats. We showed here that tumor cell injection produced mechanical and thermal hyperalgesia, and an enhanced body weight–bearing difference, which was correlated with an upregulation of p65 and P2X3R expression in lumber DRGs and a potentiation of ATP-evoked responses of tibia-innervating DRG neurons. Inhibition of NF-κB signaling using p65 inhibitor pyrrolidine dithiocarbamate, BAY-11-7082, or lentiviral-p65 short-hairpin RNA significantly attenuated CIP and reversed the activities of P2X3R. Interestingly, tumor cell injection led to a significant demethylation of CpG island in p2x3r gene promoter and enhanced ability of p65 to bind the promoter of p2x3r gene. Our findings suggest that upregulation of P2X3R expression was mediated by the enhanced binding capability of p65 with demethylated promoter of p2x3r gene, thus contributing to CIP. NF-κBp65 might be a potential target for treating CIP, a neuropathic pain generated by tumor cell–induced injury to nerves that innervate the skin. Abstract : Supplemental Digital Content is Available in the Text.Epigenetic regulations of P2X3 receptors play a crucial role in cancer pain. Targeting p65 binding to demethylated P2X3 receptor gene suppresses cancer pain.